Sintering of binderless TiN and TiCN-based cermet for toughness applications: Processing techniques and mechanical properties: A review. Issue 17 (1st December 2019) - Akinribide, O.J.; Obadele, B.A.; Akinwamide, S.O.; Bilal, H.; Ajibola, O.O.; Ayeleru, O.O.; Ringer, S.P.; Olubambi, P.A.
Abstract: This paper presents a review on sintered titanium nitride and titanium carbonitride-based cermets. TiN and TiCN based composites are remarkable class of cermets showing outstanding combination of hardness, high temperature strength and surface stability in tribology, corrosive or oxidative environments. These cermets play important roles in cutting tools and other high-temperature applications. Nonetheless, the cermets suffer some setback in toughness functionality required in cutting tools especially at high temperatures. Many researchers have worked on enhancing the hardness and toughness behaviours of TiCN using metallic binders to modify the toughness properties. The only achievement obtained was an improvement in high hardness with low toughness. This review is needed to evaluate the trends of achievement and development in the enhancement of optimum combination of hardness and toughness required in cutting tools applications. Additionally, it forecasts the essentiality of developing binderless phase TiCN with ultra-toughness that will significantly solve the deficiencies in high temperature application of TiCN as cutting tools.